장비에 따른 3차원 공간정보 품질향상 요인추출 및 집단 간 선호도에 관한 연구 - 오민균; 배상태; 김태우; 이정일; Oh, Min-Kyun; Bea, Sang-Tea; Kim, Tea-Woo; Lee, Jung-Il (지적과 국토정보, 2016)
This study analyzes the key factors of 3D spatial information in accordance with the establishment of aerial and ground equipment fusion, and the quality improvement solutions are delivered from the preference survey. Furthermore, it investigates the factors affecting the quality of the individual technical elements through the establishment of three-dimensional spatial information. It is for identifying the priority which needs to be improved, and this data will be used to identify the evaluation for factors, the technology development and its application. For this purpose, the presence or absence of equality is judged by the quantitative techniques through the preference survey of the gap between the experts of spatial information and survey and the general users who have experiences on 3D spatial information. 본 연구에서는 공중 및 지상장비에 따른 3차원 공간정보 구축의 핵심요인을 분석하고 선호도 조사를 통하여 품질 향상 방안을 도출하였다. 이는 3차원 공간정보 구축을 위한 개별 기술 요소에 대하여 품질에 영향을 미치는 요인을 조사하고, 개선이 요구되는 우선순위를 파악하여 이에 대한 요인 평가 및 대안기술 개발과 적용 등의 자료로 활용하기 위함이다. 이를 위해 3차원 공간정보를 바라보는 집단 간 견해차의 선호도 조사를 통하여 공간정보 및 측량에 종사하는 전문가 집단과 일반적으로 3차원 공간정보를 경험한 비전문가 집단을 대상으로 동일성 유무를 계량적 기법에 의해 판단하였다.